THE EFFECT OF WORK FROM HOME, MOTIVATION AND LEADERSHIP ON THE PERFORMANCE OF CIVIL SERVANTS OF SOUTHEAST MALUKU DISTRICT EDUCATION OFFICE - Kristia Kristia (Department of Management - Institut Shanti Bhuana, 2022)
The purpose of this study was to assess whether working from home, motivation, and leadership had an effect on the performance of the State Civil Apparatus at the Education Office of Southeast Maluku Regency during the Covid-19 pandemic. This research employed saturated sampling where the respondents consist of 62 employees who have experience working from home during the period January-September 2021. The data in this study were analyzed using multiple linear regression data processing techniques using SPSS version 25 for Windows. The research findings indicate that both simultaneously and partially, the variables of remote work, motivation, and leadership all significantly affect the performance of the State Civil Apparatus.